Annals of Neurology: Volume 85, Number 4, April 2019. Issue 4 (5th April 2019) - Unknown
Abstract : A photomicrograph showing innervation, stained black with immunohistochemistry for PGP9.5, in a sweat gland (stained red with Congo Red) in a normal control subject. Individuals who have mutations of the transthyretin gene causing familial amyloid polyneuropathy have little remaining PGP9.5 innervation of their sweat glands, whereas carriers had only mild fiber loss. See Chao et al., pp. 560–573 for details